The biology of medicinal resource substitution in Salvia - Ning Cui; Tiezhu Chen; Baosheng Liao; Jiang Xu; Xiwen Li (BMC, 2021)
Abstract Background The decrease of wild reserves and the sharp increase of market demand have led to resource substitution, but it is still not clear how to discover medicinal alternative resources. Here we reveal the biology of medicinal resource substitution in the case of Salvia. Methods A hypothesis was put forward that phylogeny and ecology were the main factors which determined alternative species selection. Phylogenetic analysis was performed based on chloroplast genomes. Spatial climatic pattern was assessed through three mathematical models. Results Salvia miltiorrhiza and alternative species were mainly located in Clade 3 in topology, and their growth environment was clustered into an independent group 3 inferred from principal component analysis. Correlation and Maxent major climate factor analyses showed that the ecological variations within each lineage were significantly smaller than the overall divergent between any two lineages. Mantel test reconfirmed the inalienability between phylogeny and ecology (P = 0.002). Only the species that are genetically and ecologically related to S. miltiorrhiza can form a cluster with it. Conclusions Phylogenetic relationship and geographical climate work together to determine which species has the potential to be selected as substitutes. Other medicinal plants can learn from this biology towards developing alternative resources.